Prevalência e validação dos testes para diagnóstico de Trichomonas vaginalis em mulheres grávidas, não grávidas e portadoras do HIV - Lemos, Patrícia Abreu Pinheiro de (2017)
Introduction Trichomonas vaginalis is a flagelate protozoa found in genital human secretions. Tricomoniasis is considered the most prevalent non viral sexually transmitted disease worldwide. Pregnant women and population with immunossupression had the highest frequencies in accord with literature. Purposes The presente study aimed firstly at the systematic review “Trichomonas vaginalis, genetic variation, and HIV-positive women” and secondly focused at the original article “ Association between T. vaginalis in pregant, non-pregnant and HIV-positive women” in order to: a) establish the prevalence of diagnostic techniques in 3 groups of women; b) verify whether imunossupression and/or coinfection conditions represents a risk fator for acquiring T. vaginalis; d) evaluate the accuracy of diagnostic techniques taking PCR as gold standard. Methods The study population included 309 women receiving care at 3 referral public healthcare centers in Goiânia. Pregnant women (100) at Dona Iris Maternity and General Hospital, non-pregnant women at Federal University of Goiás’ Teaching Hospital and 103 HIV-positive women in heathcare at an outpatient clinic of the Tropical Diseases Hospital in Goiânia, Goiás, Brazil. The parasite has been detected comparatively through 4 diagnostic techniques: wet mount, culture, Papanicolaou’s smear and PCR. Accuracy from all techniques was performed in the three women population and PCR was considered gold standard. Results The present study found a positive association between T. vaginalis’ frequency in HIV positive compared with non-pregnant women (ODDS RATIO (OR) 2,26). Comparisom between pregnant women and the non-pregnant women control group demonstrated no association (OR 1,07). PCR technique and wet mount presented the most elevated percentage in the pregnant and HIV positive groups correlated with the women control group. Culture presented almost the same acuracy percentages in the three groups (sensibiity) and the stainning techniques were the most sensibles however with the lowest specificities due to the vast number of false positives (FP). Precancerous lesions were associated with T. vaginalis’ presence both in pregnant and HIV positive women (OR=4,53 and OR-2,12). Conclusion T. vaginalis’ frequency in non- Abstract xvi pregant-women was 18%, in pregnant women was 19% and in HIV positive was 33%. Physiological immunossupression (pregnancy) did not represent risk factor for T. vaginalis’ infection however coinfection for HIV represented risk factor. Accuracy of diagnostic techniques (wet mount and culture) presented higher sensitivitie rates in HIV-positive women (54% e 70%). Cultured T. vaginalis stained by Quick Panoptic presented lower specificity rates in the 3 study groups.